Pengaruh Kemampuan Memahami Materi PAI Terhadap Ahklak Siswa SMAN 1 Cigombong - Astrid suwardani asmadi putri; Santi lisnawati; Kamalludin (CV. ITTC INDONESIA, 2025)
The decline of morals among some Muslims, especially teenagers in Indonesia, is a major challenge in Islamic religious education today. Moral education, which is an inseparable part of religious education, faces complex issues, especially in shaping the character and morality of the younger generation. This study aims to analyze (a) the ability to understand Islamic Religious Education (PAI) materials in 12th grade students at SMAN 1 Cigombong, (b) the condition of students' morals, and (c) the effect of the ability to understand PAI materials on students' morals at the school. This research uses the Ex-post facto method, which aims to explore the factors that influence students' morals. The results showed that: (1) The ability to understand PAI materials reached an average of 78, which is included in the “less” category; (2) Student morals showed an average score of 60, which is included in the “good” category; and (3) There was no significant influence between the ability to understand PAI materials and student morals at SMAN 1 Cigombong. Although students' understanding of PAI materials is still relatively low, this does not directly affect the quality of their morals. This finding shows the importance of a more holistic approach in Islamic religious education, which not only focuses on the cognitive aspect, but also the affective aspect and the practice of students' daily lives. Therefore, more integrative efforts are needed in strengthening moral education in schools.